Impact of medicine shortages on patients - a framework and application in the Netherlands - Doerine J. Postma; Peter A. G. M. De Smet; Kim Notenboom; Hubert G. M. Leufkens; Aukje K. Mantel-Teeuwisse (BMC, 2022)
Abstract Background Medicine shortages are often described in plain numbers, suggesting all shortages have a uniform impact. However, some shortages have a direct and serious effect on patients and need a prompt reaction from stakeholders. This study aims to create a broad framework to assess the impact of a shortage. Method We identified high impact shortages and selected exemplary shortages which we considered our learning cases. From five learning cases, we identified elements that had a potentially profound impact on one or more of these cases. We tested data saturation on the elements with another five test cases. Based on these elements, we created a framework to assess impact of shortages on patients and presented practical examples how to rate these different elements. Subsequently, we visualised the impact of these five learning cases on patients in radar charts. Results The five elements which we identified as potentially having a large impact were 1) alternative product, 2) disease, 3) susceptibility, 4) costs and 5) number of patients affected. The five learning cases rated high on different elements, leading to diverse and sometimes even opposite patterns of impact. Conclusion We created a framework for assessing the impact of a medicine shortage on patients by means of five key elements. By rating these elements, an indication of the impact can be obtained.